Extract of Teak Leaf Buds (Tectona grandis) as Natural Dyes Replacement of Eosin on HE Staining - Adrianus Ola wuan; Angelyca Florestra Tulit Bali; Ni Ketut Yuliana Sari (Poltekkes Kemenkes Kupang, 2025)
Hematoxylin and Eosin (HE) staining is a routine method in histopathology. In HE staining, eosin functions to stain the cytoplasm of the tissue. Continuous use of eosin may cause health problems due to its carcinogenic properties, thus requiring an alternative. One such alternative is teak leaf buds, which contain anthocyanin compounds. The aim of this study was to determine whether teak leaf bud extract can be used as a substitute for eosin in HE staining. The type of research used was a true experimental study with a post-test only control group design. The samples consisted of paraffin blocks, from which 10 slides were prepared: one control and nine treatment slides, with three repetitions for each concentration (20%, 30%, and 40%). Microscopic observations of HE staining using eosin showed a score of 3 (100%). Using 20% teak bud extract resulted in a score of 2 (100%), 30% concentration gave a score of 2 (33,3%) and score 3 (66,7%), while 40% concentration resulted in score 3 (100%). Kruskal-Wallis test showed eosin and teak leaf bud extract were not significantly different: for 20% concentration, p = 0,083; for 30%, p = 0,564; and for 40%, p = 1,000 (p > 0,05), indicating no significant difference.It can be concluded that 40% teak leaf bud extract is the best concentration and has the potential to replace eosin in HE staining. Future research is suggested to use 40% teak leaf bud extract with variations in staining time to further explore its potential as a substitute for eosin in histological staining.